Resource Sharing, Networking and Consortia in African Libraries (JOURNAL OF INNOVATIVE RESEARCH IN MANAGEMENT AND HUMANITIES, 2010)
This paper explores the concepts, issues and facilities offered by the libraryconsortium and shows how the library consortium makes resources available amongmember libraries. The study also identifies the possibilities and problems of building libraryconsortium in developing Africa. Recommendations suggesting models for the futureprospect of library consortia in Africa are offered.
Keywords: resource, sharing, networking, consortia